2021
DOI: 10.2463/mrms.mp.2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Malignant Breast Lesions Using High-resolution Readout-segmented Diffusion-weighted Echo-planar Imaging: Comparison with Pathology

Abstract: We aimed to investigate the performance of high resolution-diffusion-weighted imaging (HR-DWI) using readout-segmented echo-planar imaging in visualizing malignant breast lesions and evaluating their extent, using pathology as a reference.Methods: This retrospective study included patients who underwent HR-DWI with surgically confirmed malignant breast lesions. Two radiologists blinded to the final diagnosis evaluated HR-DWI independently and identified the lesions, measuring their maximum diameters. Another r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Based on these results, it can be considered that f-DWI may be a potential competitor to DCE-MRI in evaluating the morphologic features and extent of breast masses and it was thought that the use of high-resolution DWI together with c-DWI could increase the diagnostic accuracy especially in patients who cannot undergo contrast-enhanced imaging. One of the other important results of our study, parallel to the findings in the literature is the determination of the ADC values obtained with f-DWIs to be statistically lower than the ADC values obtained with c-DWIs (28,31,32). Although, this effect has been suggested to be secondary to a reduced partial volume effect of normal fibroglandular tissue and residual fat in high resolution images, the exact mechanism has not yet been fully clarified (2,11).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Based on these results, it can be considered that f-DWI may be a potential competitor to DCE-MRI in evaluating the morphologic features and extent of breast masses and it was thought that the use of high-resolution DWI together with c-DWI could increase the diagnostic accuracy especially in patients who cannot undergo contrast-enhanced imaging. One of the other important results of our study, parallel to the findings in the literature is the determination of the ADC values obtained with f-DWIs to be statistically lower than the ADC values obtained with c-DWIs (28,31,32). Although, this effect has been suggested to be secondary to a reduced partial volume effect of normal fibroglandular tissue and residual fat in high resolution images, the exact mechanism has not yet been fully clarified (2,11).…”
Section: Discussionsupporting
confidence: 83%
“…In c-DWIs, which is one of the most preferred unenhanced MRI methods, it is tried to obtain information about the quantitative values of breast lesions rather than their qualitative characteristics (26,27). However, in recent years, there have been various publications investigating the diagnostic contribution of DWIs in determining the morphological features of breast lesions (28,16,17,19,20). Kang et al concluded the potential utility of c-DWI in assessing morphologic features of lesions with high accuracy rates, which can be used for benign-malignant differentiation or for prognostic prediction (16).…”
Section: Discussionmentioning
confidence: 99%
“… 69 Single-shot EPI has been used for dMRI acquisition sequences, which limits spatial resolution and image quality. While various high spatial resolution dMRI acquisition pulse sequences have been proposedand used 70 72 in the last decades, there are remaining improvement opportunities to balance scan time, image quality, and spatial resolution.…”
Section: Image Contrast and Quantitative Imagingmentioning
confidence: 99%
“…11,12 RS-EPI is expected to improve the diagnostic accuracy of detecting PTAs on DWI as it provides less distortion, and its advantages are reported in some organs including the head and neck. [13][14][15] However, to our knowledge, there is no literature focusing on the usefulness of 3T RS-EPI for the localization and distinction of PTAs. We conducted the present retrospective study to determine whether 3T RS-EPI can reduce image distortion and improve the lesion identification in PTAs compared to 1.5T SS-EPI, and to determine whether PTAs can be differentiated from other soft-tissue structures of the head and neck region by using the ADC value.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 RS-EPI is expected to improve the diagnostic accuracy of detecting PTAs on DWI as it provides less distortion, and its advantages are reported in some organs including the head and neck. 13 15 …”
Section: Introductionmentioning
confidence: 99%